Synthesis of mono-, di- and trifunctional hydroxyl-terminated polyisobutylenes - Bohdan, Mikalai S.; Shiman, Dmitriy I.; Gaponik, Ludmila V.; Kostjuk, Sergei V. (Journal of the Belarusian State University. Chemistry, 2024)
An effective method for the synthesis of polyisobutylene with terminal hydroxyl groups was developed. The method is based on the combination of controlled cationic polymerisation of isobutylene in the presence of FeCl3 ⋅ 1.4iPrOH as co-initiator and in situ alkylation of phenol by polyisobutylene catalysed by iron(III) and aluminium chlorides. To achieve high alkylation rate and functionalisation degree in the process of polyisobutylene modification the one should proceed at room temperature and the usage of excesses of phenol complexes with chosen Lewis acids. Mono-, di- and trifunctional hydroxyl-terminated polyisobutylenes were synthesised in a broad range of molecular weights (1000–10000 g/mol) with a low polydispersity (Mw /Mn = 1.2).
Keywords: cationic polymerisation; polyisobutylene; alkylation; phenol